Pengaruh Lingkungan Kerja Fisik Dan Non Fisik Terhadap Produktivitas Kerja Karyawan Bagian Produksi CV. Shahama Tasikmalaya - Sindi Febrianti; Kusuma Agdhi Rahwana; Barin Barlian (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study is to determine and analyze the effect of the work environment on the work productivity of employees of production division of CV. Shahama Tasikmalaya. The research method used is a quantitative method with a cencus approach to 65 respondents who are employees of the production division of CV. Shahama Tasikmalaya. The types of data used are primary data and secondary data. The analytical method used in this study is multiple linear regression analysis. The result of the study prove that the work environment has a positive and significant effect simultaneously or partially on the work productivity of employees of CV. Shahama Tasikmalaya.